Engineering Geological Design of Underground Works for Upper Madi Hydroelectric Project - K.C., Prem Krishna; Panthi, Krishna Kanta (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
Himalayan geology is termed as one of the youngest tectonic formations in the world. Tunneling in this region is hence complex in nature. The very complex geology in the region offers challenges in stability of even the best located underground structures. Tunneling in weak rock is more challenging in terms of stability and application of support. Moreover, in many occasion, prediction of the rock mass has been done optimistically in most of the underground projects in Nepal. In this paper, predicted versus actual rock mass condition has been compared for two already completed projects. Based on this needed support is calculated by empirical method for the project under investigation and later on verified by numerical analysis using the software Phase2. Stability analysis is also done for both high pressure headrace tunnel and underground surge shaft. Numerical method of analysis has an added advantage over empirical and analytical methods, particularly in complex geometry. The Phase2 code and the Hoek-Brown Failure criterion have been used to determine the state of stress, strength factor and deformations around the periphery and in the tunnel walls. DOI: http://dx.doi.org/10.3126/hn.v9i0.7069 Hydro Nepal Vol.9 July 2011 27-34